Do divorcing couples become happier by breaking up? - Jonathan Gardner; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2005)
Divorce is a leap in the dark. This paper investigates whether people who split up actually become happier. Using the British Household Panel Survey, we are able to observe an individual's level of psychological wellbeing in the years before and after divorce. Our results show that divorcing couples reap psychological gains from the dissolution of their marriages. Men and women benefit equally. The paper also studies the effects of bereavement, of having dependent children, and of remarriage. We measure wellbeing using GHQ and life-satisfaction scores.
Keywords: J12; I3; 330; divorce; happiness; GHQ; life satisfaction; longitudinal data